Penerapan Sebelum Dan Sesudah Sistem Informasi Akuntansi Syariah Dengan Menggunakan Aplikasi Software Accounting Dalam Penyusunan Laporan Keuangan Bagi UMKM - INDRA, YETTI AFRIDA (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2020)
The benefits of implementing Islamic accounting in their business will make it easier for MSME players to make Islamic financial reports, evaluate performance, find out their financial position, and calculate taxes. This research is about the application of before and after the use of accounting information systems using Zahir Accounting software in the preparation of financial reports on MSMEs in Bengkulu City. This research uses a case study approach. The data used in this study are primary data obtained directly from the MSMEs through interviews. This research uses qualitative research methods, namely the method of analysis carried out by looking for the strengths that exist in the company and then compared with the Zahir Accounting software that will be recommended by the author. From the research results, it was found that some of the results of the research on the financial statements of the UMKM in Bengkulu City are currently good. MSMEs do not need to bother making financial reports manually. You don't need to make proof of a transaction receipt or invoice manually, because the accounting application can print all the evidence..